Paralogous Antirepressors Acting on the Master Regulator for Biofilm Formation in Bacillus subtilis - Chai, Yunrong (2009)
Matrix production during biofilm formation by Bacillus subtilis is governed by a gene control circuit at the heart of which are three dedicated regulatory proteins, the antirepressor SinI, the repressor SinR, and the downstream regulator SlrR. Matrix production is triggered by the synthesis of SinI, which binds to and inactivates SinR, thereby derepressing genes for matrix production as well as the gene for SlrR. Recently, two additional regulators of matrix genes were identified: SlrA, which was reported to be an activator of SlrR, and YwcC, a repressor of SlrA synthesis. We present evidence indicating that SlrA, which is a paralog of SinI, is like SinI, an antirepressor that binds to, and inactivates, SinR. We also show that SlrA does not activate SlrR for expression of matrix genes. Instead, SlrR binds to, and inhibits the activity of, SlrA. Thus, the YwcC-SlrA-SinR-SlrR pathway is a negative feedback loop in which SlrA indirectly stimulates the synthesis of SlrR, and SlrR, in turn, inhibits the activity of SlrA. Finally, we report that under standard laboratory conditions SlrA makes only a small contribution to the expression of genes for matrix production. We propose that in response to an unknown signal recognized by the YwcC repressor, SlrA transiently boosts matrix production.